Impulsive functional-differential equations with nonlocal conditions - Haydar Akça; Abdelkader Boucherif; Valéry Covachev (International Journal of Mathematics and Mathematical Sciences)
The existence, uniqueness, and continuous dependence of a mild solution of an impulsive functional-differential evolution nonlocal Cauchy problem in general Banach spaces are studied. Methods of fixed point theorems, of a C0 semigroup of operators and the Banach contraction theorem are applied.